Interaction between gene and nutrients: Nutrigenetics and Nutrigenomics - Cataño, Héctor C. (2007)
Few decades ago, several studies have described well the relation that exists between dietary habits and chronic disease, therefore the critical part of prevention disease strategy has consisted of changing the dietary habits. However, it has not been had into consideration that nutrients oi diets interact with genes. Thanks to development of nutrigenetics, and nutrigenomics the tuture dietary recommendations will have in consideration the interaction between genes and nutrients. The nutrigenetics study the influence of genetic variability in nutrient respond (interaction Gen--> Nutrient). In other hand, the nutrigenomics study the influence of nutrient in gene expression (interaction Nutrlent --> Gen). Both disciplines give rise to a new era "Molecular Nutrition" . The íncreasing knowledge of interaction gene-nutrient promises to revolutionize the handling of chronic diseases. It will be possible have better tools of diagnostics to identify precociously small alterations of homeostasis in an apparently healthy subject and to make an opportune dietary intervention which restore the homeostasis and delay the development of some disease.